The relationship between kinaesthesia, motor performance, physical fitness and joint mobility in children with and without joint hypermobility in Nigeria - Anieto, Ebuka Miracle (Department of Health and Rehabilitation Sciences, 2023)
Background: Some children with generalized joint hypermobility (GJH) develop symptoms at some point, which could negatively affect their overall health status. When GJH presents with symptoms, it is described as benign joint hypermobility syndrome (BJHS). Some of the symptoms may include pain, soft tissue injuries, and early onset osteoarthritis. The factors that may predict the development of symptoms in people with GJH have not been established. It is important to explore and identify the factors that modulate the clinical outcomes of children with joint hypermobility, and the factors that predispose some children to developing BJHS). Exploring these factors will help in establishing indicators to observe in longitudinal studies to identify causality, and in developing interventions that will be specifically targeted at influencing those modulators. Aims: to determine the relationship between kinaesthesia, motor performance, fitness and joint mobility in children, and to also determine if kinaesthesia, motor performance, fitness are different in children diagnosed with GJH compared to those who have normal mobility. Methods: a cross-sectional, analytical study was conducted involving children from two primary schools in South-Eastern part of Nigeria. The Beighton criteria were used for the classification of GJH, while using a cut-off of ≥ 6 out of the 9-maximum score. The children were allocated into two groups: children with GJH, and children with normal mobility (NM). Motor performance, fitness and kinaesthesia were measured in all the children. Motor performance and fitness were measured using the performance and fitness battery (PERF-FIT), while kinaesthesia was measured using wedges. Partial correlation was used to evaluate the relationship between the outcomes, while controlling for age and BMI. The non-parametric ANCOVA test (Quade's test) was used to evaluate the differences in the outcomes (motor performance, fitness, and kinaesthesia) between children with GJH and children with NM, while also controlling for age and BMI. Results: A total of 91 children (51.6% girls, and 48.4% boys) participated in the study. The mean age of the children was 8.20 ± 1.98. GJH was identified in a total of 35 (38.46%) children, while 56 (61.54%) children had normal mobility. GJH was more frequent in females (60.0%) than in males (40.0%). There was no statistically significant correlation between joint mobility and kinaesthesia. There was also no statistically significant correlation between joint mobility and motor performance items, as well as the fitness items. There was a statistically significant positive correlation between kinaesthesia and some motor performance items including ball bounce, ball throw and dynamic balance, as well as a significant negative correlation between kinaesthesia and one fitness item- ladder run. Furthermore, there was a statistically significant positive correlation between age and kinaesthesia (correct wedges discrimination). The study also showed that motor performance items, kinaesthesia, and most fitness items, did not differ significantly between children with GJH and children with NM. Conclusion: Joint mobility may not have a significant influence on motor performance and fitness in children that are still at their early stage of growth. Kinaesthesia may be an important factor to consider in children, as it had significant correlations with some motor performance and a fitness item. Furthermore, kinaesthesia is better when the children are older.